Current situation in providing medical care for burn injuries in Ukraine: public opinion - Chornopyshchuk, R.; Nagaichuk, V.; Kozinets, G.; Nazarchuk, O.; Turganska, O.; Khimich, S.; Zheliba, M. (Journal of Education, Health and Sport, 2022)
The results of assessment of specialized medical assistance to burn victims are presented in the article, they being based not on standard statistical figures from burn units and centers but on anonymous online survey of 486 respondents (60.5% of them - the residents of Vinnytsya region). The aim of this questionnaire-based survey was to study the level of awareness of Ukrainian population regarding the principles of providing first aid for burn injuries, as well as the availability, quality and shortcomings of current burn care in medical institutions based on the assessment of discharged patients. For this purpose, a 37-item questionnaire was developed, being divided into some blocks: general information about respondents, pre-medical aid, first medical aid, qualified medical aid and specialized medical care. According to the questionnaire, 76.9% of respondents rated the quality of medical care 5 scores by 5-score system, 17.9% - 4 scores, 5.2% - 3 scores, being indicative of rather high level of burn care, even in conditions of limited material, technical and financial resources, as well as rapid decrease of confidence in doctors in general. Online survey conducted in every region of Ukraine seems to be reasonable to make adequate assessment of study problem in the country in general.